2015
DOI: 10.1007/s13187-015-0800-9
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Outcomes of Student Field Research Experiences in Special Populations

Abstract: Global health education and training of biomedical students in international and minority health research is expending through U.S. academic institutions. This study addresses the short- and long-term outcomes of an NCI-funded R25 short-term summer field research training program. This program is designed for MPH and Ph.D. students in cancer epidemiology and related disciplines, in international and minority settings (special populations) in a recent 7-year period. Positive short-term outcome of 73 students wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…While participants identified these various qualities and attitudes being valuable for supervisors, they also indicated that the dynamic of the relationship between supervisor and trainee is critically important for effective training outcomes. This reflects other findings which state that "the quality of the supervisory relationship strongly affects the effectiveness of supervision" (20), and that the compatibility of personalities between supervisor and trainee is an important predictor of later professional outcomes for trainees in applied epidemiology (21). Similarly, the findings of our study indicate that a compatible and positive relationship between supervisor and trainee is critical for effective supervision and learning to occur.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While participants identified these various qualities and attitudes being valuable for supervisors, they also indicated that the dynamic of the relationship between supervisor and trainee is critically important for effective training outcomes. This reflects other findings which state that "the quality of the supervisory relationship strongly affects the effectiveness of supervision" (20), and that the compatibility of personalities between supervisor and trainee is an important predictor of later professional outcomes for trainees in applied epidemiology (21). Similarly, the findings of our study indicate that a compatible and positive relationship between supervisor and trainee is critical for effective supervision and learning to occur.…”
Section: Discussionsupporting
confidence: 89%
“…Further investigation in this area would be strengthened by including more objective measures of program success and linked to more objective measures of longitudinal trainee outcomes. Studies of supervision in other contexts have used measures such as trainees' later publication rates and job attainment in relevant fields, which could be explored when developing more direct indicators of efficacy in outbreak investigation training [21].…”
Section: Discussionmentioning
confidence: 99%
“…18 Studies of supervision in other contexts have assessed efficacy using measures such as trainees' publication rates and job attainment in relevant specialist fields, which could be explored in developing indicators of supervisor performance in FETPs. 19 Given the study's sample from Western Pacific and South-East Asian FETPs, this may limit the generalizability of our findings to other regions, though comparison with other findings from African and Asia-Pacific FETPs indicates similar experiences and challenges with regards to supervision. 6,7…”
Section: Challenges To Supervisionmentioning
confidence: 75%
“…In addition to medical students, global health field training is available at many institutions for public health, nursing, engineering, business, and students in other disciplines [12]. An evaluation of a National Cancer Institute-funded traineeship for cancer epidemiology graduate students selected to participate in a summer global health training program demonstrated that mentorship played a role in positive short- and long-term student outcomes as measured by student publications of their field work and employment in the field after three years [7]. It is reasonable to expect that establishing a model of considerations in a mentor-mentee relationship within the global health curriculum would not only improve student experience, knowledge, and skills, but also result in a higher likelihood of continued international engagement from the student and stronger relationships with colleagues and communities overseas.…”
Section: Introductionmentioning
confidence: 99%